The Influence of Environmental Factors on Sleep Quality in Hospitalized Medical Patients - Bano, Milena; Chiaromanni, Federica; Corrias, Michela; Turco, Matteo; De Rui, Michele; Amodio, Piero; Merkel, Carlo; Gatta, Angelo; Mazzotta, Gabriella; Costa, Rodolfo; Montagnese, Sara (Frontiers in Neurology, 2014)
Introduction. Sleep-wake disturbances are common in hospitalised patients but few studies have assessed them systematically. The aim of the present study was to assess sleep quality in a group of medical inpatients, in relation to environmental factors, and the switch to daylight saving time. Methods. Between March and April 2013, 132 consecutive inpatients were screened and 99 (76±11 yrs; hospitalization: 8±7 days) enrolled. They slept in double or quadruple rooms, facing South/South-East, and were qualified as sleeping near/far from the window. They underwent daily sleep assessment by standard questionnaires/diaries. Illuminance was measured by a luxmeter at each patient’s eye-level, four times per day. Noise was measured at the same times by a phonometer. Information was recorded on room lighting, position of the rolling shutters and number/type of extra people in the room. Results. Compliance with sleep-wake assessment was poor, with a range of completion of 2-59%, depending on the questionnaires. Reported sleep quality was sufficient and sleep timing dictated by hospital routine; 33% of the patients reported one/more sleepless nights. Illuminance was generally low, and rolling shutters half way down for most of the 24 hours. Patients who slept near the window were exposed to more light in the morning (i.e. 222±72 vs. 174±85 lux, p<0.05 before the switch; 198±72 vs.141±137 lux, p<0.01 after the switch) and tended to slept better (7.3±1.8 vs. 5.8±2.4 on a 1-10 scale, before the switch, p<0.05; 7.7±2.3 vs. 6.6±1.8, n.s. after the switch). Noise levels were higher than recommended for care units but substantially comparable across times/room types. No significant differences were observed in sleep parameters before/after the switch. Conclusions. Medical wards appear to be noisy environments, in which limited attention is paid to light/dark hygiene. An association was observed between sleep quality and bed position/light exposure, which is worthy of further study.